Myocardial Perfusion Scintigraphy in Ischemic Heart Disease - Sonia María Sánchez Valcarcel; Katia Ravelo Llanes; Iván Rodríguez Cortina; Geovedy Martínez García; Cesia Rivera Garmendia (Revista Finlay)
Background: ischemic heart disease has a high prevalence and mortality in Cuba and in developed countries. Myocardial perfusion scintigraphy is a non-invasive diagnostic method that facilitates diagnosis and medical decision-making. Objective: to demonstrate the value of myocardial perfusion scintigraphy in the ischemic heart disease prognosis. Method: a descriptive, prospective longitudinal section study was carried out in 180 patients, in which myocardial perfusion studies were performed to detect ischemia, from January 2018 to December 2019 at the Center for Surgical Medical Research. The variables studied were: clinical-demographic characteristics (age, sex), atherogenic risk factors and chest pain. The qualitative variables were expressed in frequency and percentage and the continuous quantitative variables in mean and standard deviation values according to their distribution and chi square. The 95 % confidence interval was taken, with a p <0.05 for the acceptance and interpretation of the results. Results: the 53.3 % of the patients were men and 78.3 % suffered from arterial hypertension. The physical stress test was performed to detect ischemia at 76.1 %. The negative result predominated in 58.9 %; with a clinical evolution at one year of only 2.8 % with ischemic events. Ischemia was demonstrated in myocardial perfusion in 41.1 %, confirming significant coronary obstructive lesions in 82.4 %. After one year of clinical evolution, 97.3 % developed ischemic events. The drop> 10 % in the post-stress left ventricular ejection fraction showed ischemic events in 100 % of the patients. Conclusions: myocardial perfusion scintigraphy is a reliable non-invasive technique in the ischemic heart disease diagnosis. It provided long-term prognostic security after the negative myocardial perfusion result. The fall in the post-stress left ventricular ejection fraction behaved as a predictive variable of future cardiac events.